2015
DOI: 10.1590/s1806-92902015000700005
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile, chemical composition, and sensory effects of crude glycerin on the longissimus dorsi of crossbred Boer goat kids

Abstract: -The objectives of this trial were to evaluate the fatty acid profile, chemical composition, and sensory effects of crude glycerin on the longissimus dorsi muscle of crossbred Boer goat kids. Twenty crossbred Boer goat kids (20.8±2.9 kg of BW at slaughter) were used in a completely randomized block design to determine the effect of partial replacement of corn by crude glycerin on chemical composition, longissimus dorsi muscle fatty acid profile, and sensory characteristics of meat. Kids were penned individuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
0
0
1
Order By: Relevance
“…This suggest that the meat is of good quality, as it is within the quality standards of lamb meat. Other studies have reported no differences in the muscle chemical composition of lambs fed diets containing crude glycerin (Rocha et al, 2015).…”
Section: Resultsmentioning
confidence: 76%
“…This suggest that the meat is of good quality, as it is within the quality standards of lamb meat. Other studies have reported no differences in the muscle chemical composition of lambs fed diets containing crude glycerin (Rocha et al, 2015).…”
Section: Resultsmentioning
confidence: 76%
“…Los cortes comerciales y la calidad de la carne no fueron influenciados (p>0.05) por la inclusión de glicerol hasta 9.60% en la dieta (Cuadro 6). No obstante, Alves e Dias et al (2018) indican que niveles de 8.63% de glicerol en la MS provoca disminución de los cortes comerciales como la pierna, lomo y costillas; sin embargo, Rocha et al (2015) verificaron que hasta 9.60% de glicerol en la MS no afecta la composición química de la carne, excepto para mineral, que presenta un efecto lineal, disminuyendo su concentración al aumentar la inclusión de glicerol en la dieta. En ese sentido, Oliveira et al (2020) recomiendan ajustar la composición mineral de las dietas en corderos en engorde alimentados con 10% glicerina bruta (9.16% de glicerol) para mejor conservación de los valores nutricionales, debido a que, a ese nivel de glicerol, aumenta la concentración de sodio en el músculo longissimus lumborum de corderos.…”
Section: Resultados Y Discusiónunclassified